2017
DOI: 10.1016/j.stemcr.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Dermatopontin in Bone Marrow Extracellular Matrix Regulates Adherence but Is Dispensable for Murine Hematopoietic Cell Maintenance

Abstract: SummaryThe hematopoietic marrow microenvironment is composed of multiple cell types embedded in an extracellular matrix (ECM). We have explored marrow ECM using mass spectrometry and found dermatopontin (DPT), a small non-collagenous ECM protein, to be present. We found that DPT cooperates with other ECM proteins to promote hematopoietic cell adherence in vitro on plastic as well as OP9 stromal cells. We generated constitutional DPT−/− mice that were viable and had no peripheral lympho-hematopoietic abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It was hypothesized that DPT was acting to help tether HSC to the stromal layer and perhaps allow for improved contact between HSC and growth factors produced by stroma augmenting paracrine signals. We also previously observed that DPT can directly bind HSPC and modulate HSPC adherence to OP9 murine stroma cells 28 . Conversely, in the context of HSPC adherence to endothelial cells, we found the reverse effectthe presence of DPT led to reduced adherence.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…It was hypothesized that DPT was acting to help tether HSC to the stromal layer and perhaps allow for improved contact between HSC and growth factors produced by stroma augmenting paracrine signals. We also previously observed that DPT can directly bind HSPC and modulate HSPC adherence to OP9 murine stroma cells 28 . Conversely, in the context of HSPC adherence to endothelial cells, we found the reverse effectthe presence of DPT led to reduced adherence.…”
Section: Discussionmentioning
confidence: 64%
“…We focused on genes expressed at the cell membrane or extracellularly secreted versus the transcription factors as the former would be more likely modulate intrinsic HSPC activity. One particular gene found to be elevated in irradiated niche cells was dermatopontin (dpt) a small (23 kDa) non-collagenous extracellular matrix (ECM) protein that we have previously described in the murine marrow ECM 28 . Other prior work has shown that murine DPT can play a positive role in HSPC ex vivo culture expansion 29 ; though, we have shown DPT knockout mice have no steady state hematopoietic deficits and do have increased peripheral HSPC mobilization capacity suggesting a role in cell trafficking 28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our molecular analyses also show the potential of EA to modulate over 1,600 BM genes that are mainly related to extracellular matrix receptor interaction, B cell and toll-like receptors signaling, and the p53 and NF-kB pathways. Indeed, the extracellular matrix is critical to hematopoiesis and the response of hematopoietic cells to neurotransmitters and growth factors ( 24 , 80 ). For instance, fibronectin is important for the adhesion and proliferation of hematopoietic and erythroid progenitors ( 81 ), whereas adiponectin can inhibit myelomonocytic cell expansion ( 82 ) and Col1a1 and Col1a2 are produced by BM stromal cells to define BM hematopoietic niche microenvironment ( 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%